Loss and Bereavement: The Role of the Teacher in the Primary School - Christiana Kartselou (Progress in Language, Literature and Education Research Vol. 9, 2024)
For the child, the loss is experienced as a painful and traumatic experience. This paper deals with the role of the teacher towards the grieving child. As the school space is de facto a space where students spend a large part of their daily life, it is particularly important to determine in which ways, through which techniques the modern school will contribute decisively to the modification of students’ perceptions of loss and how he will handle his students who experience the specific situations, taking into account that there is a deficit in the Greek educational reality and the required attention has not been given to the specific taboo subject, which teachers often find difficult to handle. The present study was based on bibliographic data, such as empirical, theoretical studies, or other bibliographic research and writings. The study concludes on three basic principles of managing a grieving child a) to help children feel safe and recognize the reality of death, b) to create an environment that will facilitate children to talk about their feelings, c) to form appropriate learning opportunities aiming to educate children about death.